Gentamicin Induced Biochemical Changes in Auditory Cortex of Adult Albino Rats - Rehan, Asad Mohammad; Nazim, Nasir; Kamran, Afzal; Waqas, Sami; Haider, Jafari Fahim (Journal of Asian Scientific Research, 2013)
Background: The aminoglycoside antibiotics have been the drug of choice for the treatment of tuberculosis and resistant cases of septicaemia, but their use has been selective and restricted due to their known toxicities specially the ototoxicity and nephrotoxicity. Aminoglycosides have good activity against many multi-drug resistant Gram negative bacilli. Gentamicin, due to it cost effectiveness has been used in most of the trials as compared to other aminoglycoside. Most studies documented the peripheral toxicities of gentamicin without any concern of central neurotoxicity. Objective: the study was planned to observe the effects of gentamicin on the biochemical parameters (specially, sodium, potassium and calcium) in auditory cortex of albino rats. Methods: It was an experimental study. Twenty rats were randomly divided in two groups; Group I (Experimental: n = 10) received intramuscular injection of Gentamicin for twenty one days and Group II (Control: n =10) received normal saline intramuscularly. Tissue samples were taken from the area around lateral sulcus of rat cortex i.e. auditory cortex. The samples were homogenized and digested in concentrated nitric acid (100mg/ml). The supernatant solution was used for estimation of sodium and potassium by Flame Photometry and calcium level by the method of Clark and Collip. Results: The calcium level was increased; the sodium level was decreased while potassium level remained unaltered.Conclusion: Alteration in sodium and calcium level demonstrates central neurotoxicity of gentamicin.